Al-Islām wa al-Madd wa al-Jazr fī al-‘Alāqāt bayn al-Dīn wa al-Dawlah fī Indonesia - Ismatu Ropi (Studia Islamika, 2016)
This article reviews the complex contestation between religion and state in terms of the Muslims role in the formation of nation state since Indonesia’s independence. The article’s first part discusses the emergence of new middle-class Muslims that played a key role in the Islamization process and contribute to the emergence of Islamist attitudes and behavior. These attitudes tend to be strengthened and lead the potential latent extremism endangering multiculturalism and multireligious life in Indonesia. The article’s second part focuses on the long history of the Muslims role as majority groups in the formation of the constitution’s nomenclature relating to the position of religion in the state system. The new middle-class Muslims also have a desire to achieve their dreams exposing the greater portion of religion in public sphere. It can be seen from the strengthening of those Muslims activists in the parliament to transform the comprehensive meaning of the concept of God.DOI: 10.15408/sdi.v23i2.3715